Eruption cycles of Mount Etna triggered by seasonal climatic rainfall. (January 2022) - Sahoo, Sambit; Tiwari, Deepak K.; Panda, Dibyashakti; Kundu, Bhaskar
Abstract: The ability to mitigate and predict volcanic risk is a long-standing question in the Geosciences' community, while the extent of volcanic activity may be regulated by a predictable and periodic external excitation induced by seasonal rainfall, hydrological loading, or Moon-Sun gravitational force. Moreover, the complex stress-triggering, hydro-mechanical coupling in response to seasonal rainfall, and associated feedback mechanism with deep magmatic process remains enigmatic and indeed deserves more attention in view of recent climate change scenario. In this letter, a compelling scenario of seasonal rainfall-triggered eruption cycles of Mount Etna (Italy) is found and presented on the eastern coast of Sicily which continuously erupting since last 200 kyr. Results show that the seasonal rainfall significantly weakened the Mount Etna edifice and initiated mechanical tensile failure in the complex magmatic plumbing system and adjacent flank surface by changing the pore pressure build-up, probably promoting dyke intrusion and eventual triggering of eruptive cycle. Further, the possibility of seasonal hydrological loading on the Mount Etna volcano and adjacent flank region, hydrological load-induced sliding along the impermeable outer 'shell' of the flank are discussed, and the effect of tidal stress perturbations on the eruptions cycle cannot be ruled out completely. Graphical Abstract: ga1 Highlights: Increase in pore pressure due to seasonal rainfall weakens the Mount Etna edifice. Increased pore pressure generates tensile stress to open fractures in the edifice. High pore pressure facilitates fault resonance by lowering magma chamber overpressure. Subtle higher eruption ( 63%) occurs when the Earth is closer to the apogee. No correlation between fortnight tidal stress and eruption sequence at Mount Etna.